Effects of nanoscale surface modification and triplet energy shielding of a single layer solution processed blue phosphorescent organic light emitting diode by using Triton X-100 - Yeoh, K.H. (Elsevier, 2013)
The effects of triplet energy shielding and nanoscale surface modification using Triton X-100 in a single layer solution processed blue phosphorescent organic light emitting diodes (PhOLED) was investigated. It was found that with 3.2 wt% Triton X-100 doping, the power efficiency of the device doubled at brightness of 1000 cd/m2. The insertion Triton X-100 provides separation between guest–host which reduced back energy transfer from the high triplet of FIrpic (2.7 eV) to the low triplet of PVK host (2.5 eV). Atomic force microscopy (AFM) indicates that phase separation of Triton X-100 modified the emissive layer (EML) surface morphology. This surface modification roughened the film surface at the EML/cathode interface. These combined effects improves the performance of the solution processed blue PhOLED.